Respuesta :

Answer:

see explanation

Step-by-step explanation:

Given f(x) then the derivative f'(x) is

f'(x) = lim( h tends to 0 ) [tex]\frac{f(x+h)-f(x)}{h}[/tex]

      = lim( h to 0 )[tex]\frac{x+h+\frac{1}{x+h }-(x+\frac{1}{x} ) }{h}[/tex]

      = lim(h to 0) [tex]\frac{x+h+\frac{1}{x+h}-x-\frac{1}{x} }{h}[/tex]

      = (lim(h to 0) [tex]\frac{h+\frac{1}{x+h}-\frac{1}{x} }{h}[/tex]

      = lim( h to 0 ) [tex]\frac{hx(x+h)+x-(x+h)}{hx(x+h)}[/tex]

      = lim( h to 0 ) [tex]\frac{hx(x+h)+x-x-h}{hx(x+h)}[/tex]

      = lim(h to 0 ) [tex]\frac{hx(x+h)}{hx(x+h)}[/tex] - [tex]\frac{h}{hx(x+h)}[/tex]

Cancel the numerator/denominator of first fraction and h in the second

= lim ( h to 0 ) 1 - [tex]\frac{1}{x(x+h)}[/tex] ( let h go to zero ), then

f'(x) = 1 - [tex]\frac{1}{x^2}[/tex]

ACCESS MORE